Functional improvements in patients with lymphangioleiomyomatosis after sirolimus: an observational study - Yongzhong Zhan; Lisha Shen; Wenshuai Xu; Xiuxiu Wu; Weihong Zhang; Jun Wang; Xue Li; Yanli Yang; Xinlun Tian; Kai-Feng Xu (Orphanet Journal of Rare Diseases, 2018)
Abstract Background Sirolimus has been shown to be effective in patients with lymphangioleiomyomatosis (LAM). We wish to summarize our experience using sirolimus and its effectiveness in LAM patients. Methods We analyzed data from 98 patients who were diagnosed with definite or probable sporadic LAM based on the European Respiratory Society diagnosis criteria for LAM in 2010 at Peking Union Medical College Hospital and who had received sirolimus during January 2007 to June 2015. The data before and after the initiation of sirolimus therapy included pulmonary function tests, arterial blood gas analysis, 6-min walking distance (6MWD), size of chylous effusion and renal angiomyolipomas (AML), St. George’s Respiratory Questionnaires (SGRQ) and vascular endothelial growth factor-D (VEGF-D) levels. Serum levels of sirolimus and adverse events were collected. Results Median follow-up was 2.5 years. Most patients had forced expiratory volume in 1 s (FEV1) values less than 70% predicted or symptomatic chylothorax. The mean changes before and after the initiation of sirolimus were − 31.12 ± 30.78 mL/month and 16.11 ± 36.00 mL/month (n = 18,p = 0.002) for FEV1 change, and − 0.55 ± 0.60 mmHg/month and 0.30 ± 1.19 mmHg/month (n = 17, p = 0.018) for PaO2 change. 6MWD improved from 358.8 ± 114.4 m to 415.6 ± 118.6 m (n = 46, p = 0.004) and SGRQ total score from 57.2 ± 21.0 to 47.5 ± 22.8 (n = 50, p < 0.001). The median VEGF-D concentration decreased to 1609.4 pg/mL from 3075.6 pg/mL after sirolimus therapy (n = 41, p < 0.001). Patients with sirolimus trough levels of 5–9.9 ng/mL had an increase in FEV1 (p < 0.05). Sixty-five percent of patients (13/20) had almost complete resolution of chylous effusions. The most frequent adverse events were mouth ulcers, menstrual disorder, hyperlipidemia and acneiform rash, all were mild. Conclusion Long-term use of sirolimus is safe in patients with LAM. LAM patients with FEV1 less than 70% predicted and symptomatic chylothorax are suitable for receiving sirolimus therapy. The maintaining serum trough levels of sirolimus are recommended between 5 to 9.99 ng/mL.